(untitled) (Health Renaissance, 2017)
Background: Ponseti method of manipulation and casting has been standard non operative method of treatment for idiopathic clubfoot. We have conducted this study to find out whether Ponseti method of correction can be taught to doctors working at district hospital. Objective: To assess the knowledge, familiarize the Ponseti method of correction and to decrease the need of surgery regarding the congenital talipesequinovarus. Method: We conducted prospective study among doctors working in the district hospitals of eastern Nepal. We assessed knowledge and practice regarding clubfoot management before and after the intervention by questionnaire based method. The data were analyzed using before and after difference for magnitude and paired t test for significance. Result: 13 doctors were included in the study. Among 13 participants, one (7.69%) had formal orthopedic training. Only 30% of the participants had more than 60% correct response regarding questionnaires regarding knowledge of clubfoot. 40% of participants had done referral of cases to orthopedic centre. One (7.69%) of the participants had applied Ponseti cast. 61% percent of the participants responded more than 60% correctly at the final follow up at one year. Conclusion: The study shows that the knowledge and practice regarding Clubfoot correction is inadequate and hence teaching of Ponseti method was useful in the district hospital. Health Renaissance 2015;13(2): 144-152